Evaluating the effects of maternal exposure to benzene, toluene, ethyl benzene, and xylene on oral clefts among offspring in Texas: 1999–2008. Issue 8 (25th July 2013) - Ramakrishnan, Anushuya; Lupo, Philip J.; Agopian, A.J.; Linder, Stephen H.; Stock, Thomas H.; Langlois, Peter H.; Craft, Elena
ABSTRACT BACKGROUND There is evidence from previous studies that maternal occupational exposure to hazardous air pollutants (HAPs) is positively associated with oral clefts; however, studies evaluating the association between residential exposure to these toxicants and oral clefts are lacking. Therefore, our goal was to conduct a case‐control study examining the association between estimated maternal residential exposure to benzene, toluene, ethyl benzene, and xylene (BTEX) and the risk of oral clefts among offspring. METHODS Data on 6045 nonsyndromic isolated oral cleft cases (3915 cleft lip with or without cleft palate [CL ± P] and 2130 nonsyndromic isolated cleft palate [CP] cases) delivered between 1999 and 2008 were obtained from the Texas Birth Defects Registry. The control group was a sample of unaffected live births, frequency matched to cases on year of birth. Census tract‐level estimates of annual average exposures were obtained from the U.S. Environmental Protection Agency 2005 Hazardous Air Pollutant Exposure Model (HAPEM5) for each pollutant and assigned to each subject based on maternal residence during pregnancy. Logistic regression was used to assess the relationship between estimated maternal exposure to each pollutant (BTEX) separately and the risk of oral clefts in offspring. RESULTS High estimated maternal exposure to benzene was not associated with oral clefts, compared with low estimated exposure (CL ± P adjusted OR = 0.95; 95% CI = 0.81 − 1.12; CP adjusted OR = 0.85; 95% CI = 0.67 − 1.09). Similar results were seen for the other pollutants. CONCLUSION In our study, there was no evidence that maternal exposure to environmental levels of BTEX was associated with oral clefts. Birth Defects Research (Part A) 97:532‐537, 2013. © 2013 Wiley Periodicals, Inc.